2011
DOI: 10.1080/00380768.2011.623282
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphate and sulfate fertilizers on selenium uptake by wheat (Triticum aestivum)

Abstract: The objective of this study was to investigate whether oxyanionic phosphate (P) and sulfate (S) fertilizer management could influence selenium (Se) uptake by wheat (Triticum aestivum) in medium and high Se areas. Field studies were established at two locations for two growing seasons in central South Dakota, USA. Phosphate fertilizer was applied using three different methods (banded with seed, surfacebroadcasted in the fall, or surface-broadcasted in the spring) using six different P rates. Sulfate fertilizers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 29 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…However, current literature reports on the relationship between plant Se uptake and P levels and acquisition have shown conflicting results ( Table 2). The hydrogen phosphate ion can significantly reduce Se(IV) absorption from the soil by competition, however, increasing soil-solution Se concentrations, while Se in soil solution is easily absorbed by plants (Lee et al, 2011;Zhou et al, 2015). Zhang et al (2017) reported that P fertilization together with Se(IV) could significantly reduce Se accumulation in wheat in calcareous soil, but in the case of P fertilization together with Se(VI), there was increased Se accumulation in wheat.…”
Section: The Role Of Phosphorus In the Regulation Of Se Bioavailabilimentioning
confidence: 99%
See 1 more Smart Citation
“…However, current literature reports on the relationship between plant Se uptake and P levels and acquisition have shown conflicting results ( Table 2). The hydrogen phosphate ion can significantly reduce Se(IV) absorption from the soil by competition, however, increasing soil-solution Se concentrations, while Se in soil solution is easily absorbed by plants (Lee et al, 2011;Zhou et al, 2015). Zhang et al (2017) reported that P fertilization together with Se(IV) could significantly reduce Se accumulation in wheat in calcareous soil, but in the case of P fertilization together with Se(VI), there was increased Se accumulation in wheat.…”
Section: The Role Of Phosphorus In the Regulation Of Se Bioavailabilimentioning
confidence: 99%
“…Dhillon and Dhillon (2000) reported that the application of 0.8 t hm –2 gypsum to selenite-rich soil significantly decreased total Se accumulation in rice, while increasing S content, with minimal reductions in Se concentration in grains and straw by 35 and 36%, respectively. S application can significantly inhibit Se(IV) absorption and accumulation ( Lee et al, 2011 ; Liu et al, 2016a ), but a hydroponic experiment also showed that selenite and sulfate had no antagonistic effects on Se uptake ( Li et al, 2008 ). This suggests that the inhibitory effect of S fertilizer on Se(IV) uptake and accumulation by plants under soil cultivation depends on other processes rather than competitive adsorption.…”
Section: Se Interactions With Macronutrient Elements (N P and S)mentioning
confidence: 99%
“…Previous studies have focused more on Se-sulfur (S), Mo-S, Se-phosphorus (P) and Mo-P interactions in soil and solution culture, but little attention has been paid to the possible interactions of Mo-Se in soil or in hydroponic culture (Alhendawi et al 2005;Mora et al 2008;Togay et al 2008;Lee et al 2011a). Although Mo and Se do not belong to the same periodic group, they are both absorbed by plants in form of anions.…”
Section: Introductionmentioning
confidence: 97%
“…This indicates that there are differences between various parts of B. napus in the biconcentration capacity of Se. It was demonstrated in a hydroponic experiment that selenite and sulfate had no antagonistic effects on Se uptake (Zhang et al 2006;Li et al 2008), but in a field experiment, Lee et al (2011b) reported that the Se concentration in the grain of wheat grown in naturally high Se areas decreased at least 53.3% by using 80 kg S ha −1 . Cartes et al (2006) also found that the Se concentration in the shoots of ryegrass (Lolium perenne cv.…”
Section: Discussionmentioning
confidence: 99%